Chaperone Copolymer Assisted G-Quadruplex-Based Signal Amplification Assay for Highly Sensitive Detection of VEGF - Jialun Han; Chenxin Fang; Ping Ouyang; Yang Qing; Yuxing Yang; Haiyu Li; Zhencui Wang; Jie Du (Biosensors, 2022)
Vascular endothelial growth factor (VEGF) is a critical biomarker in the angiogenesis of several cancers. Nowadays, novel approaches to rapid, sensitive, and reliable VEGF detection are urgently required for early cancer diagnosis. Cationic comb-type copolymer, poly(L-lysine)-graft-dextran (PLL-g-Dex) accelerates DNA hybridization and chain exchange reaction while stabilizing the DNA assembly structure. In this work, we examined the chaperone activity of PLL-g-Dex to assist G-quadruplex-based fluorescent DNA biosensors for sensitive detection of VEGF. This convenient and effective strategy is based on chitosan hydrogel, c-myc, Thioflavin T (ThT), VEGF aptamer, and its partially complementary strand. The results show that chaperone copolymer PLL-g-Dex significantly promotes the accumulation of G-quadruplex and assembles into G-wires, allowing an effective signal amplification. Using this method, the detection limit of VEGF was as low as 23 pM, better than many previous works on aptamer-based VEGF detection. This chaperone copolymer-assisted signal amplification strategy has potential applications in the highly sensitive detection of target proteins, even including viruses.